Antibacterial Activity Of Spilanthes Acmella Flower Extracts (safe) Against Streptococcus Mutans - Siti Aisyah Abd Ghafar; Muhammad Fikhry Mohd Salehuddin; Nur Syamimi Syuhada Che Awang; Rohazila Mohamad Hanafiah (UPM, 2024)
Non-Indexed Publication